Granulomatous panuveitis following prolonged silicone oil tamponade - A Clinicopathological study - Ayushi Mohapatra; Jyotirmay Biswas (Indian Journal of Pathology and Microbiology)
An enucleated specimen of a silicone oil-filled globe, showing migration of oil globules into the intraretinal, choroidal, and ciliary body areas, surrounded by multinucleated giant cells suggestive of panuveitis on histopathological evaluation, was reported.